Les stagiaires au sein du service de conservation-restauration de Galliera, musée de la Mode de la Ville de Paris : former un étudiant stagiaire à la conservation préventive - Charlotte Piot (In Situ : Revue de Patrimoines, 2012)
The department for preservation and conservation of Galliera receives an average of 17 trainees a year. Their varied profiles can be grouped in three categories: pupils of schools of fashion or sewing and student in art history, mostly in fashion speciality; pupils committed in a course in preventive conservation (maintenance of the heritage or management of collection); and finally students longing to become conservators. According to their course, their notions of preventive conservation are very uneven: the program of training course and the supervision have to adapt itself. The training of the trainees also presents a beneficial return for the department: constant requirement and questioning.